2011
DOI: 10.1042/bj20111221
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and structural analysis of positive allosteric modulation of the ionotropic glutamate receptor GluA2

Abstract: Positive allosteric modulators of the ionotropic glutamate receptor-2 (GluA2) are promising compounds for the treatment of cognitive disorders, e.g. Alzheimer's disease. These modulators bind within the dimer interface of the LBD (ligand-binding domain) and stabilize the agonist-bound conformation slowing receptor desensitization and/or deactivation. In the present study, we employ isothermal titration calorimetry to determine binding affinities and thermodynamic details of binding of modulators of GluA2. A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 34 publications
3
90
0
Order By: Relevance
“…In addition to the binding of ifenprodil and zinc to NMDA receptor ATD dimers, a large body of crystallographic work reveals that the LBD dimers of AMPA receptors bind allosteric drugs which either attenuate desensitization or slow deactivation, while kainate receptor LBD dimers bind modulatory ions. For AMPA receptors more than 20 crystals structures have been solved for GluA2 and GluA3 complexes with a chemically diverse range of novel allosteric modulators, including ligands which differentiate flip and flop splice isoforms (55, 111118). All of these ligands bind to a series of five overlapping hydrophobic and hydrophilic sites at the base of the LBD dimer assembly, but the stoichiometry varies from 1:1 or 2:1 drug molecules per dimer, depending on the ligand structure and binding sites targeted.…”
Section: Novel Allosteric Modulatorsmentioning
confidence: 99%
“…In addition to the binding of ifenprodil and zinc to NMDA receptor ATD dimers, a large body of crystallographic work reveals that the LBD dimers of AMPA receptors bind allosteric drugs which either attenuate desensitization or slow deactivation, while kainate receptor LBD dimers bind modulatory ions. For AMPA receptors more than 20 crystals structures have been solved for GluA2 and GluA3 complexes with a chemically diverse range of novel allosteric modulators, including ligands which differentiate flip and flop splice isoforms (55, 111118). All of these ligands bind to a series of five overlapping hydrophobic and hydrophilic sites at the base of the LBD dimer assembly, but the stoichiometry varies from 1:1 or 2:1 drug molecules per dimer, depending on the ligand structure and binding sites targeted.…”
Section: Novel Allosteric Modulatorsmentioning
confidence: 99%
“…22 Briefly, Escherichia coli Origami B (DE3) cells were transformed with the GluA2-LBD-L483Y-N754S pET-22b(+) plasmid. Cells were grown in LB medium to an OD 600 of 0.9…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…It has been suggested that differential occupancy of these subsites by the various classes of positive modulator determines their different mechanisms of action. The classes of positive modulator compounds that have been characterized include: the benzothiadiazides (cyclothiazide, IDRA21, BPAM-97), the benzamides (aniracetam and CX614), the benzoxainones, and the biarylsulfonamides (LY404187, CMPDA, CMPDB; Fernandez et al, 2006; Jin et al, 2005; Krintel et al, 2012; Mueller et al, 2011; Sun et al, 2002; Timm et al, 2011). Although new and higher affinity compounds are being identified at a rapid pace, there appears to be a significant lag in the ability to translate novel compounds tested in vitro to viable targets for clinical trials (Lynch et al, 2011; Swanson, 2009; Ward et al, 2010) with only a few AMPA receptor positive modulators making it into clinical trials in the U.S. (CX516, Lynch et al, 1997; CX717, Wesensten et al, 2007; http://clinicaltrials.gov/ct2/results?term=AMPAkine).…”
Section: Introductionmentioning
confidence: 99%